2018
DOI: 10.3906/tar-1801-95
|View full text |Cite
|
Sign up to set email alerts
|

Isoflavone profile diversity in Korean wild soybeans ( Glycine soja Sieb. & Zucc.)

Abstract: Isoflavones prevent the incidence of cancer, reduce cardiovascular problems, and decrease menopausal symptoms. In soybean (Glycine soja Sieb. & Zucc.) seeds, the content is greatly affected by growing conditions. The variations in soy-isoflavone content were investigated by growing 346 Korean wild soybean accessions from natural habitats under the same agroclimatic conditions. Highperformance liquid chromatography was used to measure the profiles of six soy-isoflavones, i.e. glycosides (daidzin, glycitin, geni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 35 publications
0
9
0
1
Order By: Relevance
“…The detailed composition of isoflavones was identified using a LTQ Orbitrap XL hybrid mass spectrometer (Thermo Fisher Scientific, Kanagawa, Japan) coupled to a Prominence UFLC TM C18 column system (Shimadzu, Kyoto, Japan) equipped with a binary pump, a degasser, an autosampler and a thermostatted column compartment (Tsukamoto et al ). The extracts were applied by injecting 20 µ l of 7·5‐fold (v/w) solutions of 80% aqueous methanol (v/v).…”
Section: Methodsmentioning
confidence: 99%
“…The detailed composition of isoflavones was identified using a LTQ Orbitrap XL hybrid mass spectrometer (Thermo Fisher Scientific, Kanagawa, Japan) coupled to a Prominence UFLC TM C18 column system (Shimadzu, Kyoto, Japan) equipped with a binary pump, a degasser, an autosampler and a thermostatted column compartment (Tsukamoto et al ). The extracts were applied by injecting 20 µ l of 7·5‐fold (v/w) solutions of 80% aqueous methanol (v/v).…”
Section: Methodsmentioning
confidence: 99%
“…Apart from saponins, other compounds such as soy isoflavones, polyphenols, flavonoids, proanthocyanidins, and phenolic acids have also been analyzed in large-scale wild soybean collections in Korea as well as in wild soybeans from other natural habitats. These studies identified unique germplasm accessions with higher amounts of these beneficial/desirable secondary metabolites that will be an important resource for future breeding (Ha et al 2018;Nawaz et al 2018;Tsukamoto et al 2018). In additional to beneficial metabolites, trace harmful metabolites such as raffinose are also found in soybean.…”
Section: Progress On Soybean Molecular Breeding In the Republic Of Koreamentioning
confidence: 98%
“…The wild soybean soyasaponin mutants from CWLGC have been used to identify and characterize the genes involved in the saponin biosynthesis pathway, e.g., Sg-1 locus (CWS2133), sg-5 locus (CWS5095), and Sg-6 locus [33,105,[107][108][109]. In addition to saponins, wild soybean accessions at the CWLGC have also been screened for the presence of Kunitz trypsin inhibitor polymorphism, alpha-linolenic acid concentration, and soyisoflavone profile diversity [110][111][112][113]. Furthermore, the germplasms have been used to functionally characterize two seed-specific flavonoid glycosyltransferases and a β-amyrin synthase gene [109,114].…”
Section: In Situ Conservation Of G Soja At Cwlgcmentioning
confidence: 99%